A Bibliometric Exploration Whistleblowing Intention Research in Corporate Governance and Ethics - Judijanto, Loso; Wifasari, Septi (The Es Accounting And Finance, 2025)
This study presents a comprehensive bibliometric analysis of scholarly research on whistleblowing intention within the context of corporate governance and business ethics. Utilizing data from the Scopus database covering the period 2000 to 2024, a total of [insert number] relevant publications were analyzed using VOSviewer to identify patterns in authorship, thematic development, collaboration networks, and keyword trends. The results indicate that whistleblowing intention has evolved from being a narrowly focused ethical concern to a multifaceted area of inquiry intersecting with psychology, organizational behavior, public administration, and leadership studies. Prominent contributors such as Miceli, Near, and Dworkin have laid the theoretical foundation, while emerging themes like psychological safety, religiosity, and public service motivation reflect a broadening of perspectives and methodologies. Geographically, research remains dominated by Western countries, though participation from emerging economies is increasing. This study offers strategic insights for academics, practitioners, and policymakers by identifying influential scholars, core themes, and future research opportunities to strengthen whistleblowing mechanisms and ethical decision-making in organizations.